2009
DOI: 10.1097/ajp.0b013e31817fc62d
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of Parents and Children on Characteristics of Pediatric Headache, Other Pains, Somatic Symptoms, and Depressive Symptoms in an Epidemiologic Study

Abstract: The examined potential moderator variables did not elucidate processes underlying the differences in child and parent agreement. There is no convincing evidence that the children's appraisal is less valid than their parents'. In summary, parents' reports cannot be viewed as a substitute for children's reports in pediatric pain and health assessment. Instead, each perspective represents a unique subjective reality and as such, both are of importance for research on pediatric pain and other health variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 25 publications
8
38
1
1
Order By: Relevance
“…This occurred despite the fact that the CBT intervention did not involve the parents directly (they participated only in the first epilepsy education module). Health-related quality of life (QoL) research has shown that there is a lack of concordance between proxy and child reports of QoL, with proxy reports reporting a lower QoL compared with child reports [31][32][33][34]. Fathers and mothers of children with epilepsy rate QoL similarly but differently from the child [32].…”
Section: Discussionmentioning
confidence: 99%
“…This occurred despite the fact that the CBT intervention did not involve the parents directly (they participated only in the first epilepsy education module). Health-related quality of life (QoL) research has shown that there is a lack of concordance between proxy and child reports of QoL, with proxy reports reporting a lower QoL compared with child reports [31][32][33][34]. Fathers and mothers of children with epilepsy rate QoL similarly but differently from the child [32].…”
Section: Discussionmentioning
confidence: 99%
“…musculoskeletal, headache, stomach-ache etc., overall the results from these studies are broadly similar to those of ours. Three of the four studies [8][9][10] reported generally poor agreement between parent and child ratings, while the last reported somewhat higher concordance [16]. Three studies [9,10,16] also found that children reported pain more often (and of greater intensity) than their parents, in the fourth study this relationship held for girls aged 12 and over but not for boys or younger girls.…”
Section: Discussionmentioning
confidence: 72%
“…Three of the four studies [8][9][10] reported generally poor agreement between parent and child ratings, while the last reported somewhat higher concordance [16]. Three studies [9,10,16] also found that children reported pain more often (and of greater intensity) than their parents, in the fourth study this relationship held for girls aged 12 and over but not for boys or younger girls. The influence of age and gender on concordance of the ratings was variable across the studies, but the finding that agreement between the ratings was better where the condition was more severe was reported in all studies, as in the present study.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…For these reasons, adolescent perceptions cannot be substituted with parent reports but, rather, each perspective needs to be considered for effective medical management. Studies examining parent and child reports of health factors have found differences in perceptions, but results have been inconsistent, and no clear predictors or moderators of parent-child agreement have emerged [20][21][22]. Studies examining consistency of parent and child reports specifically in transplantation were not identified in the literature; however, understanding how they each perceive medications is critical for optimal management.…”
Section: Parent and Child Reportsmentioning
confidence: 92%